Antioxidant potential of hydrolyzed polyphenolic extracts from tara (Caesalpinia spinosa) pods - Chambi, Flor (2013)
The antioxidant potential of tara pod extracts rich in gallotannins submitted to chemical hydrolysis was evaluated. The increase in the release of gallic acid from the tara pod extracts during the hydrolysis process reached a maximum ratio of free gallic acid/total phenolics of 94.1% at 20 h, at this point, 100% hydrolysis degree (HD) was obtained. After 4 h of hydrolysis (38.8% of HD) the highest antioxidant capacity was obtained reaching values of 25.9, 23.8 and 8.8 μmol trolox equivalent/mg gallic acid equivalent measured by ABTS, FRAP and ORAC methods. Lipophilicity diminished from 0.8 to 0.3 (log P value). In addition, the antioxidant efficacy of 100 ppm total phenolics of hydrolyzates at 9 h (93.7% of HD) and 20 h showed to be significantly more efficient than a similar concentration of the synthetic antioxidant TBHQ to retard soybean oil oxidation. These results indicate that 4 and 9 h of chemical hydrolysis of tara pod extracts under the tested conditions are sufficient to obtain a product with good antioxidant properties to be used as an alternative source of antioxidants.